PENGUKURAN TINGKAT KEPUASAN PENGGUNA SISTEM INFORMASI DENGAN MODEL MATEMATIS NON LINEAR - Endro Prihastono (Jurnal Ilmiah Dinamika Teknik, 2011)
This research is nucleus core perceive models application nonlinear to evaluate satisfaction of information system which they use. This model is wearable as a means of to measure satisfaction of asking for user personate responder to give a value depicting satisfaction store. Response of this attributes is combined linearly is henceforth formed by model which representative in measurement of store; level satisfaction of user to information system which they use. Step is solving of this research need two data aggregate. First is primary data, continued with data of secondary as reinforcement. This data is applied at linear model and five model of[is nonlinear as comparator. Of this result we earn to do anticipation test nonlinear model more effective in predictive mount satisfaction of consumer as a whole relate to information system which they use. For this, we exploit Coefficient value of Determine as size measure according to mathematical model non paid attention linear. Keywords: Information System, Linear Mathematic Model, Non-Linear Mathematic